1998
DOI: 10.1021/ma971829+
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of 1-Oxaspiro[2.5]octa-4,7-dien-6-ones

Abstract: The polymerization of six spiro compounds such as 1-oxaspiro[2.5]octa-4,7-dien-6-one (OSODO), spiro[anthrone-10,2‘-oxirane] (SAO), and 5,7-dibromo- (Br 2 -OSODO), 5,7-di-tert-butyl- (tBu 2 -OSODO), 5,7-difluoro- (F 2 -OSODO), and 4,5,7,8-tetrachloro-1-oxaspiro[2.5]octa-4,7-dien-6-ones (Cl 4 -OSODO) were examined. Spiro compounds which carry substituents at the 4 and 8 positions or bulky substituents at the 5 and 7 positions such as SAO, tBu 2 -OSODO, and Cl 4 -OSODO were reluctant to undergo polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The quinones evaluated and used in the epoxidation reaction were extracted from the heartwood of Tabebuia spp. (Tecoma) and purified by recrystallization from ethanol as described in literature (Eistert et al 1962; Kubo et al 1998; Roush et al 1998), producing 14 compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quinones evaluated and used in the epoxidation reaction were extracted from the heartwood of Tabebuia spp. (Tecoma) and purified by recrystallization from ethanol as described in literature (Eistert et al 1962; Kubo et al 1998; Roush et al 1998), producing 14 compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Eight naphthoxiranes were synthesized from the reaction of quinone in the presence of sodium hydride as the reducing agent in dimethyl sulphoxide (DMSO) (Sigma-Aldrich ® ) and further, trimethylsulphonium iodide was added under an inert atmosphere (Fig. 1) (Kubo et al 1998).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…A fluorine-containing PPO derivative has much potential as new polymeric materials since it has excellent performances due to a PPO backbone bearing fluorine substituents. It was reported that poly(2,6-difluoro-1,4-phenylene oxide) ( 2 ) was synthesized by anionic polymerization of 5,7-difluoro-1-oxaspiro[2.5]octa-4,7-dien-6-one . This method, however, involves tedious multistep procedures including monomer synthesis and, hence, may not be suitable for preparative synthesis of 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that poly(2,6-difluoro-1,4phenylene oxide) (2) was synthesized by anionic polymerization of 5,7-difluoro-1-oxaspiro[2.5]octa-4,7-dien-6one. 12 This method, however, involves tedious multistep procedures including monomer synthesis and, hence, may not be suitable for preparative synthesis of 2. Very recently, we have found that 2,6-difluorophenol (1) was polymerized by peroxidase catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous papers, we reported a novel synthetic method for 2,6-disubstituted poly(1,4-phenylene oxide)s using oxaspiro compounds as starting materials (Scheme ). , Our proposed polymerization mechanism is shown in Scheme . The propagation reaction consists of two reaction steps.…”
Section: Introductionmentioning
confidence: 99%